Ocean in motion! : surfing and the science of waves - Mason, Paul. (Mankato, Minn. : Capstone Press, 2008)
Examines the science behind ocean waves and the sport of surfing.
The biggest ride? -- Where waves come from -- Friend and foe -- How waves break -- Catching a wave -- Turning -- Welcome to the Green Room -- Riding big waves -- Tow-in surfing -- Wiping out -- Water like concrete -- Brr! Ice-cold surfing -- Ripped away.
Includes bibliographical references (p. 31) and index.
4.7
3-6
Keywords: Ocean currents -- Juvenile literature; Ocean waves -- Juvenile literature; Wave-motion, Theory of -- Juvenile literature; Ocean currents; Ocean waves; Waves; Ocean currents; Ocean waves; Waves